(untitled) (ENTHYMEMA, 2023)
In 1949 the florentine publishing house Sansoni published an anthology under the title “Orfeo: il Tesoro della lirica universale” which includes lyrics translated from more than thirty languages ​​and throughout the centuries, beginning with the origins (III millennium BC, with the Babylonian poem Enuma Eliš), until reaching the modern age, passing through all periods and literary currents. With a disseminating and ecumenical desire and considering translation a necessity, this collection has thousands of texts translated into Italian. With regard to literature in the Spanish language, many hitherto unpublished versions are presented, with an important segment dedicated to works written by women and translated into Italian: In difesa delle donne —by Piero Raimondi— is the translation of Hombres necios que acusáis a la mujer sin razón… by Sor Juana Inés de la Cruz (1648-1695), a redondilla that opens the way to a series of topics that are still current, such as those related to the question of women in society and their relationship with power male.